Computer Assistant Substantive Test Model In Audit Of Government Institution Financial Statements - Putri, Diana Rino; Ismanu, Sidik; Haris, Zainal Abdul (AGUSPATI Research Institute, 2021)
This study aims to determine how big of a substantive test role in improving the quality of audit financial report of government agency (state university). Substantive testing can improve the perceived quality of the audit. The research method used in the preparation of this thesis is applied research. The type of research is R&D/Research and Development. This study uses secondary data that has research data sources from financial databases at State University which contains activity expenditure components. The data collection method used in this study is the documentation method. Results of this study indicate that substantive testing can improve the quality of audit based on procedures that have been done in the field from processing the SAS and BMN databases then run through the ACL application.